Deficiencies of Course Management Systems: The WebCT Vista Attitudinal Survey - Hannafin, Robert D.; Ioannou, Andri (My University, 2007)
Course management systems (CMSs) support thousands of courses at colleges and universities worldwide, delivering fully online courses as well as supplementing traditional faceto- face instruction. It is possible that CMSs have introduced so much new functionality so fast that users have not had a chance to seriously reflect on what they need or want. Perhaps users are understandably giddy about the instructional tools they now have at their fingertips, and have not yet critically examined these tools. We developed a WebCT Vista Attitudinal Survey to measure user satisfaction with the tool and perceived usefulness of specific new features currently unavailable in WebCT Vista. We piloted the survey with 234 college students who used WebCT Vista as a supplementary of a face to face course. Results provide evidence that CMSs are still evolving tools, and need accommodations and improvements.
Keywords: CMSs; WebCT Vista Attitudinal Survey